The Soong sisters - Cheung, Yuen-Ting.; Law, Alex.; Ng, See Yuen. (Hong Kong Solar Films, 1996)
A biographical account of the three Soong sisters, Ai-ling, Ching-ling, and Mei-ling, who became Mrs. H. H. Kung, Mme. Sun Yat-sen, and Mme Chiang Kai-shek, respectively. Set in China, it starts at Sun Yat-sen's rise to power, to his death, to Chiang Kai-shek's rise to power, to the Japanese invasion, to the end of Chiang Kai-shek's reign, and the establishment of Taiwan, and shows how the sisters helped shape modern China's history.
VHS.
Cast: Maggie Cheung, Michelle Khan, Vivian Wu, Jiang Wen, Winston Chou, Kuo Chiuwu.
First published in 1941 by Doubleday.
Keywords: Kung, Ai-ling (Sung) -- 1888-1972.; Sun, Ching-ling (Sung) -- 1890-1981.; Chiang, Mei-ling (Sung) -- 1892-.; Statesmen's spouses -- China -- Biography; China -- History; History